The use of a killer factor in the selection of hybrid yeast strains - Vondrejs, V; Psenicka, I; Kupcová, L; Dostálová, R; Janderová, B; Bendová, O (Folia biologica, 1983)
A new selection method of yeast cell hybrids, based on the application of yeast killer factors, has been developed in the model system of induced protoplast fusion of Saccharomyces cerevisiae superkiller strain T158C (alpha, his-) and different sensitive strains. The method is comparable in its efficiency to the currently used selection techniques based on the auxotrophy or respiration deficiency of the parental cells. Selection by means of a killer factor, when compared to other methods, has the following advantages: (1) Sensitivity to a killer factor is a current natural property of most of the yeast strains. (2) Killer strains of different species of yeast are available and the killer character can be easily transmitted from strain to strain. (3) Hybrid cells produce a killer factor (K+) and are resistant to it (R+). Both these properties are easily and independently testable. (4) Hybrid cells can be cured of the "killer character" by growth at elevated temperatures. Therefore the killer character can also serve as a temporary marker for the purposes of selection of hybrid cells and can be eliminated when no longer desired. On an example of interspecific fusion of strain T158C of S. cerevisiae and strain P9 of S. uvarum the procedure has been shown to be advantageous particularly for the construction of new industrial yeast strains because mutagenesis of the original industrial strain is not required.
Keywords: killer faktory kvasinek; Saccharomyces cerevisiae; Saccharomyces cerevisiae - proteiny; Cell Survival; Saccharomyces cerevisiae Proteins; mykotoxiny; Killer Factors, Yeast; Mycotoxins; fungální proteiny; viabilita buněk; Fungal Proteins